A simple route to vinyl-functionalized hyperbranched polymers: Self-condensing anionic copolymerization of allyl methacrylate and hydroxyethyl methacrylate. (18th August 2015) - Yang, Hongjun; Bai, Tao; Xue, Xiaoqiang; Huang, Wenyan; Chen, Jianhai; Qian, Xiaolei; Zhang, Guangzhao; Jiang, Bibiao
Abstract: Vinyl-functionalized hyperbranched polymers (HBPs) have attracted much attraction because their pendant vinyl groups can be further modified for a required application. However, the syntheses of these polymers are difficult, because the cross-linking is inevitable during the polymerization reaction. The present work reports a new, facile, one-step strategy for the synthesis of vinyl-functionalized HBPs v ia the self-condensing anionic copolymerization of commercially available allyl methacrylate and hydroxyethyl methacrylate with a monomer conversion approaching 100% at room temperature. The hyperbranched structures were confirmed by triple-detection size exclusion chromatography. The pendent vinyl groups of the resulting polymer were successfully modified by a "thiol-ene" reaction. This method provides a facile approach for preparing vinyl-functionalized HBPs with excellent monomer conversions under mild conditions, and will be useful in materials chemistry. Graphical abstract: Highlights: Commercially available monomers were employed to synthesize vinyl-functionalized HBPs. The monomer conversion was as high as 100% without crosslinking. The polymerization could proceed under mild conditions.